Cross-age study on secondary school students’ views of stars - Bitzenbauer, Philipp; Navarrete, Sarah; Hennig, Fabian; Ubben, Malte; Veith, Joaquin M. (Physical Review Physics Education Research, 2023)
Research in astronomy education has uncovered that many learners possess limited and fragmented understanding of stars. The corresponding misconceptions manifest in various areas such as star formation, size, the relationship between stars and planets, and their position in space and have been shown to persist across different age groups and educational settings, highlighting the need for further investigation. This paper presents the findings of an empirical study that examines secondary students’ views of stars and their evolution throughout their secondary school education. We designed and evaluated an instrument for assessing students’ views of stars in five domains (stars and the solar system, formation and evolution of stars, general properties and motion of stars, (sub-)stellar objects, as well as color and brightness). The instrument creation process involved several steps, including literature-based item development, an expert survey with faculty members, and a quantitative pilot study with a sample of N=390 secondary school and college students. This process led to a final version of the instrument that exhibits good psychometric properties. We used this new instrument in a cross-age study to investigate the alignment of secondary students’ ideas about stars with scientific views across different stages of secondary education. The sample of this main study comprised a total of N=366 learners, including 148 lower (aged 13–14 years), 151 middle (aged 15–16 years), and 67 upper (aged 17–18 years) secondary school students. Our study findings reveal a progressive development of students’ perspectives on star-related topics throughout their school education: Using analyses of variance and conducting pairwise post hoc comparisons, we observed a statistically significant increase in the proportion of responses aligning with scientific views across all aspects of stars examined in this study, as students progressed from lower secondary to upper secondary levels. We further report on widely held views of stars among our study participants that do not align with the scientific views and discuss the implications of our findings for both educational research and practic

Introducing quantum physics concepts and Dirac notation at the secondary school level: Insights into student reasoning from an acceptance survey - Hennig, Fabian; Tóth, Kristóf; Veith, Joaquin; Bitzenbauer, Philipp (Physical Review Physics Education Research, 2024)
Evidence from physics education research suggests that the introduction of a formalistic description of quantum phenomena can be beneficial to student learning, particularly in terms of helping students move away from naive realist views of quanta or space-Time descriptions of quantum phenomena. However, the mathematical requirements for mastering quantum formalism are typically far beyond the scope of secondary school education. Therefore, in previous research, we have proposed a reduced Dirac notation tailored to the capabilities of secondary school students, which is included in a novel teaching-learning sequence. However, the cognitive processes of students when confronted with an introduction to quantum physics via a reduced Dirac notation have not been thoroughly investigated: In particular, it seems important to investigate whether this approach is actually beneficial to students' learning and to explore the learning difficulties students are likely to encounter in such a setting. This paper contributes to this research gap by reporting the findings of an acceptance survey: N=14 learners participated in one-on-one interviews following a protocol consisting of four cyclical phases (information phase, acceptance evaluation, paraphrasing phase, and application phase). The findings of our study indicate that the instructional elements within our new teaching-learning sequence were generally well accepted by students but also revealed learning difficulties that students may encounter. Thus, on the one hand, the findings of this study pave the way for future research on students' learning of quantum physics using Dirac notation. On the other hand, the in-depth findings reported here may guide teachers in designing learning environments that introduce Dirac notation at the upper secondary school and introductory university levels.
CRIS-Team Scopus Importer:2024-12-06

Mathematical sense making of quantum phenomena using Dirac notation: its effect on secondary school students functional thinking about photons - Bitzenbauer, Philipp; Hennig, Fabian; Tóth, Kristóf; Joaquin M., Veith (EPJ Quantum Technology, 2024)
Previous research has consistently demonstrated that students often possess an inadequate understanding of fundamental quantum optics concepts, even after formal instruction. Findings from physics education research suggest that introducing a mathematical formalism to describe quantum optical phenomena may enhance students’ conceptual understanding of quantum optics. This paper investigates whether using formal descriptions of quantum optics phenomena – such as photon anticorrelation at a beamsplitter or single-photon interference in a Michelson interferometer – expressed in Dirac notation, can support secondary school students in developing functional thinking about photons. To investigate this, we conducted a clusterrandomized field study, comparing the improvement in functional thinking between 67 students in the intervention group, who were taught using both qualitative and quantitative reasoning, and 66 students in the control group, who were taught using only qualitative reasoning. The results indicate that mathematical formalism can indeed promote functional thinking about photons. However, the comparison between the intervention and control groups revealed that the control group exhibited a greater increase in functional thinking than the intervention group. In response to these findings, we conducted a follow-up study aimed at gaining a deeper understanding of the cognitive load associated with both approaches. Specifically, we compared the intrinsic and extraneous cognitive load of 71 students in the intervention group with those of 65 students in the control group. The data analysis revealed that the two groups had statistically significant differences in intrinsic cognitive load while the extraneous cognitive load did not difer statistically significant, indicating a higher mental effort associated to the quantitative reasonin

Nanoscience and -technology in secondary education: A systematic literature review - Bitzenbauer, Philipp; Schmid, Judith Maria; Joaquin M., Veith; Truong, My Hanh; Straulino, Michael; Winkler, Bianca; Hennig, Fabian (Eurasia Journal of Mathematics, Science and Technology Education, 2023)
This article provides a review of empirical research into nanoscience and -technology (NST) education at the secondary school level with regards to (a) teaching strategies or laboratory experiments implemented and evaluated for their impact on student learning about nanotechnology aspects, (b) concept inventories and methods used to assess students’ conceptual understanding, as well as (c) students’ conceptions and learning difficulties. A database search was used to identify corresponding studies published over the last decade (2012-2021) of which eleven were included in the synthesis for further analyses after screening for eligibility. The analysis revealed that learning difficulties regarding NST topics such as the differentiation between size and scale, the surface area to volume ratio or size dependent properties are widely prevalent among learners according to the current state of the literature. While our analysis identified emerging perspectives for future research with regards to the development of psychometrically characterized concept inventories in particular and empirical investigations into students’ learning progressions on nanoscience concepts in more general, a huge effort has already been put into the development of teaching concepts or laboratory experiments suitable for secondary school classrooms.

Spooky action at a distance? A two-phase study into learners’ views of quantum entanglement - Brang, Michael; Franke, Helena; Greinert, Franziska; Ubben, Malte S.; Hennig, Fabian; Bitzenbauer, Philipp (EPJ Quantum Technology, 2024)
Quantum entanglement is a challenging concept within the field of physics education, often eluding a full grasp by both educators and learners alike. In this paper, we report findings from a two-phase empirical study into the views of entanglement held by pre-service physics teachers and physics students from various universities. In the first phase, we utilized a questionnaire consisting of open-ended questions which was completed by 31 pre-service physics teachers. The study participants’ ideas were explored using qualitative content analysis which led to the creation of rating scale items used in study phase 2. These items were administered to a broader cohort including 73 physics university students in order to capture the learners’ agreement or disagreement with the questionnaire statements, and hence, helped to validate and substantiate the in-depth insights from study phase 1. Key findings revealed widespread accurate notions, like the need to consider the entire system when examining entangled states. However, less elaborated views were also identified, including ideas such as that measurements of entangled states always show perfect (anti-)correlation. Another striking observation was the confusion between quantum entanglement and superposition. In the case of quantum teleportation, many participants seemed to have a basic grasp of the concept, although a number of misconceptions were apparent, notably the idea that quantum entanglement enables faster-than-light communication. Practically, the findings can assist educators in anticipating and addressing widespread (mis-)conceptions, paving the way for more effective instruction in quantum mechanics and its real-world applications, such as quantum cryptography and computing.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Empirical study; Entanglement; Quantum physics; Teleportation